Multi-omics analysis reveals gut microbial and metabolic signatures in metabolic dysfunction-associated steatotic liver disease - Maimaitiyiming, Muyesaier; Maihemuti, Sulitanguli; Aierken, Tangnuer; Abulimiti, Gulizhati; Aibaidula, Tuersinayi; Guan, Yaru; Simayi, Abudoukeyoumu; Aimaiti, Maiwulan; Wang, Xingfu; Abuduaini, Abula; Aishan, Yierpan (Frontiers in Microbiology, 2025)
IntroductionThe high incidence rate of metabolic dysfunction-associated steatotic liver disease (MASLD) has been a big burden on public health globally.MethodsTo explore microbial and metabolic characteristics of MASLD, we performed 16S rDNA sequencing and untargeted metabolomics on 138 stool samples from MASLD patients. Through the construction of multi-omics featuremaps, we identified relevant changes in microbial and metabolic signatures and evaluated potential clinical value in MASLD.ResultsThe result showed that the high-fat, high-protein dietary pattern in MASLD patients is one of the reasons for the upregulation of Parabacteroides merdae abundance. And it can increase the branched-chain amino acid catabolic capacity in MASLD patients, thereby improving metabolic syndrome and increasing the abundance of beneficial bacteria to improve the intestinal microbiota balance. Then, the downregulation of Lachnospiraceae bacterium in MASLD patients may lead to intestinal inflammatory responses. Moreover, its increasing abundance might result in heightened appetite in MASLD patients, which leads to insulin resistance and liver damage. And the increasing in glycerophospholipid (GP) metabolites in the gut of MASLD patients is highly correlated with metabolic disorders and disease progressionassociated with hepatic fat accumulation and inflammatory responses (AUC > 0.9). Therefore, the levels of GP metabolites in the stool of MASLD patients serve as a reliable diagnostic biomarker for fatty liver and represent a potential target for the diagnosis and treatment of MASLD.DiscussionAfter analysis of gut microbiota and metabolites, we found that Lactobacillus johnsonii down-regulated in MASLD drives 2,6-Dichlorohydroquinone accumulation, provoking toxic buildup and accelerating disease progression.